Pengaruh Model Cooperative Integrated Reading And Composition (CIRC) Berbantuan Peta Konsep terhadap Pemahaman Isi Bacaan Siswa Kelas IV SDN 13 Toboali - Khoiriah, Nuria Sapitri; Asyraf Suryadin; Vika Martahayu (JBES (Journal Basic Education Skills), 2025)
The purpose of the study was to determine the effect of the integrated cooperativereading and writing model assisted by concept maps on students' understanding of readingcontent of Grade IV SD N 13 Toboali. The type of research is quasi-experimental (pseudoexperimental) using a non-equivalent control group pretest-posttest research design structure.The subjects in this study were 59 grade V students of SD Negeri 6 Kelapa who were dividedinto two, namely 29 students in the experimental class and 30 students in the control class.Data collection techniques and instruments in the form of test questions. The analysistechnique uses the independent samples t test. The results of the research show that there is aninfluence of the integrated cooperative model of reading and writing assisted by concept mapson the understanding of the reading content of Class IV students at SD N 13 Toboali. This isproven by the tvalue of 5.584 which is greater than the ttable of 1.672 (tvalue>ttable). The averagevalue of the experimental posttest was 78.2328 and the average value of the control posttestwas 65.0233. This comparison of average scores shows that there is an influence of theintegrated cooperative model of reading and writing assisted by concep